Impact of Acute Surgical Unit in Appendicectomy Outcomes (Medical Forum Monthly, 2024)
Objective: To determine the impact of acute surgical unit in appendicectomy outcomes in our hospital.Study Design: Prospective / cross-sectional studyPlace and Duration of Study: This study was conducted at the SMBB Medical College and Sindh Government Lyari General Hospital, Karachi from January 2017 to December 2017.Materials and Methods: The sample size of study was 100 taking prevalence to 32.5%. All patients with Age > 18 yrs, patients presenting with signs and symptoms of appendicitis in outpatient or emergency department were included. Patients with going home against advice and bleeding disorders were excluded.Results: Out of 100 patients enrolled in study there were 45% males and 55%females. The mean age was 36.9 ± 9.67years. Patients were shifted from emergency to theatre in 6.91± 1.22 hours, while the mean duration of hospital stay of patients was 2.95± 0.75 days. The complication rate in our study was 18%. Only 10% patients presented with negative appendicectomy.Conclusion: Acute surgical unit is associated with decreased patients’ morbidity due to early appendicectomy with decreased length of stay and postoperative complication